Occupational Stress among Radiographers Working in Tertiary Care Hospital in Udupi and Mangalore (Medico Legal Update, 2020)
Introduction: Occupational stress can negatively impact an individual and is associated with a wide rangeof physical and mental effects resulting in psychosocial and biomechanical stress. Moreover, health careworkers have been reported to have a great deal of stress mainly due to the shift duties and increasedworkload.Objectives: Therefore the study aimed to determine the psychosocial predictors of stress among radiographersin tertiary care hospitals of Udupi and Mangalore. Data was collected from 55 radiographers from threetertiary care hospitals using a standard questionnaire published by the UK health and safety (HSE). A scoreand an aggregate score was generated for each item as well as each of seven sets of working condition like“job demands, control, support from managers, support from peers, role, change and relationships”. Theanalysis tool published by the HSE was used to analyze data.Results: The indicator analysis tool recommended 11 “psychosocial work conditions” that requiredimprovement. On an aggregate level from the seven psychosocial working conditions ‘relationship’ and‘Demand’ category warranted improvement.Conclusion: The study showed majority categories being identified as “good and need to maintainperformance”. However that main predictors of occupational stress was found to be excess workloadfollowed by relationship conflicts among co-workers.